Pengaruh akupuntur pada keluhan ischialgia di Assauna Terapi Kabupaten Jeneponto - Armin Susanto; Leny Candra Kurniawan; Puspo Wardoyo; Cantika Mahadini (NERSMID : Jurnal Keperawatan dan Kebidanan, 2026)
This study was conducted to examine the impact of acupuncture therapy on sciatica complaints at Assauna Therapy Center in Jeneponto Regency. The research employed a descriptive and action research design using a qualitative approach. Data were obtained directly from the research subjects and analyzed based on the researcher's interpretation without prior secondary processing. The findings indicated that acupuncture therapy contributed to the reduction of sciatica symptoms, including lower back pain radiating to the buttocks and down the left leg. Following the therapy, the patient no longer experiences a sensation of body heaviness. Physical mobility improved significantly, allowing the patient to stand, walk, sit, and lie down comfortably in an upright or straight position. In addition, tenderness or pressure-related pain in the left lumbar region was no longer present.